Textbook of Arthropod Anatomy - Snodgrass, R. E. (Cornell University Press, 2019)
The facts of arthropod structure are presented in clear, easy-to-use fashion in this text by R. E. Snodgrass. Examples of each of the classes from trilobites to insects are given. Musculature and mechanism of legs, eyes, feeding apparatus, body, head, and organs of digestion, excretion, and reproduction are described and illustrated.Over 640 drawings, most of them by the author, are arranged in 88 figures.